2016
DOI: 10.1002/2211-5463.12102
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long noncoding RNA SPRY4‐IT1 correlates with tumor progression and poor prognosis in cervical cancer

Abstract: The identification of cancer‐associated long noncoding RNA (lncRNA) is critical for us to understand cancer pathogenesis and development. The aim of this study was to evaluate the expression profile of the lncRNA SPRY4‐IT1 in cervical cancer and to identify its clinical significance in cancer progression. The expression levels of SPRY4‐IT1 in cervical cancer tissues were measured by quantitative real‐time PCR, and its correlation with overall survival of cervical cancer patients was analyzed statistically. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Sensitivity to cisplatin, therefore, was predicted to be mediated by DNA repair pathways (Rosell et al ., ). In view of the roles of FEN1 in multiple repair processes, such as BER (Simpson et al ., ), nonhomologous end‐joining (Cao et al ., ), HR (Hu et al ., ; Liu et al ., ), NER (Herrero et al ., ; Mocquet et al ., ; Zhao et al ., ), and mismatch repair (MMR; Liu et al ., ), it was pertinent to speculate that the high level of FEN1 expression in tumors contributed to intrinsic or acquired drug resistance. To test this hypothesis, we performed drug‐sensitive experiments in A549 lung cancer cells with different FEN1 levels.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity to cisplatin, therefore, was predicted to be mediated by DNA repair pathways (Rosell et al ., ). In view of the roles of FEN1 in multiple repair processes, such as BER (Simpson et al ., ), nonhomologous end‐joining (Cao et al ., ), HR (Hu et al ., ; Liu et al ., ), NER (Herrero et al ., ; Mocquet et al ., ; Zhao et al ., ), and mismatch repair (MMR; Liu et al ., ), it was pertinent to speculate that the high level of FEN1 expression in tumors contributed to intrinsic or acquired drug resistance. To test this hypothesis, we performed drug‐sensitive experiments in A549 lung cancer cells with different FEN1 levels.…”
Section: Resultsmentioning
confidence: 99%
“…15 In addition, elevated serum HOTAIR was implicated in late stage tumours, adenocarcinomas, lymphatic vessel infiltration, and lymph node metastasis. 17,18 In this study, lncOGFRP1 was first found to be highly expression in CC, but it was not associated with the patient's prognosis. 15 In contrast, GAS5 is downregulated in CC tissues, which is significantly associated with advanced cancer progression and has been identified as an independent biomarker of clinical status in patients with CC.…”
Section: Prognosis and Progressionmentioning
confidence: 69%
“…16 In addition, TUSC8, SPRY4-IT1, and lncRNA-LET are also considered as promising markers for CC. 17,18 In this study, lncOGFRP1 was first found to be highly expression in CC, but it was not associated with the patient's prognosis. This result may be related to the small sample size.…”
Section: Prognosis and Progressionmentioning
confidence: 69%
“…Cao et al (77), showed that SPRY4-IT1 expression is a good candidate marker for discriminating between tumor tissue and normal tissue and for predicting poor prognoses in patients with cervical cancer.…”
Section: Spry4-it1 Spry4-it1mentioning
confidence: 99%